Development of liquid urea ammonium nitrate fertilizer foliar application system for enhanced nutrient use efficiency - BIJARNIYA, HITESH; KHURA, TAPAN KUMAR; MANI, INDRA; KUSHWAHA, H L; LANDE, SATISH D; SARKAR, SUSHIL KUMAR (The Indian Journal of Agricultural Sciences, 2019)
A tricycle type manually operated foliar applicator was developed with ground clearance of 74.15 cm that can be operated on standing wheat crop having row spacing of 20-22 cm. The physical properties of urea ammonium nitrate (UAN) with 3% N were found nearly equal to water with respect to dynamic viscosity, surface tension and specific gravity of UAN. Based on pressure, discharges requirement and corrosiveness of UAN, reciprocating typePVC pump (2 no.) with capacity of 4.53 l/min each was selected for the sprayer. Three type of nozzles, i.e. flat fan, stream jet SJ7 and stream jet SJ3 were evaluated in terms of discharge, spray pattern and spray angle at different heights and pressures. Spray pattern and uniformity of spray distribution of nozzles (flat fan, stream jet SJ3 and SJ7) were determined on patternator test rig. Flat fan nozzles showed most uniform pattern at 2 kg/cm2 pressure and 500 mm nozzle height, whereas streamjet SJ7 showed maximum uniformity at 1.6 kg/cm2 and 600 mm height. Streamjet SJ3 nozzles were found suitable for low boom height and directed application of fertilizer. Variation in discharge of nozzles among the boom was observed less than 10% while operated in field. Field capacity of the developed foliar applicator was found 0.3 ha/h. Operating pressure of 1.5 kg/cm2 was found ergonomically suitable with an average heart rate and energy expenditure of 119 beats/min and 26.7 kJ/min, respectively for operating the prototype. The break-even point (BEP) and payback period (PBP) of developed foliar applicator were estimated as 113.43 h/year and 4 years at the operational cost of Rupees 94.68/ha.